THE USE OF MULTIMEDIA TOOLS IN TEACHING THE RECEPTIVE SIDE OF FOREIGN LANGUAGE - Abdullaeva Shakhlo Sayfievna (Western European Studies, 2024)
This article investigates the effectiveness of multimedia tools in enhancing the development of receptive skills (listening and reading comprehension) in foreign language learning. It explores the advantages of multimedia resources, including increased engagement, improved motivation, and exposure to authentic language. The paper examines various multimedia tools such as audio recordings, video clips, interactive websites, and educational software. Additionally, it discusses pedagogical strategies for integrating these tools into classroom instruction, focusing on activities that promote active listening and close reading
Keywords: Foreign language learning; Receptive skills; Multimedia tools; Reading comprehension